Tinjauan Ushul Fiqh tentang Status Kepemilikan Aset Digital Non-Fungible (NFT) dalam Perspektif Al-milkiyyah - Ipando, Ogi Marsenal; Bahrudin, Moh.; Hilal, Syamsul (Jurnal Hukum Ekonomi Syariah, 2025)
This paper examines the concept of al-milkiyyah (ownership) in relation to digital assets, specifically Non-Fungible Tokens (NFTs), from the perspective of Uṣūl al-Fiqh. The study aims to determine the legal status of ownership and the validity of NFT transactions within the framework of contemporary Islamic jurisprudence. Employing a normative legal research method with conceptual, normative, and sectoral approaches, this study draws upon classical fiqh literature, contemporary fatwas, and analyses of blockchain technology. Secondary data are qualitatively and comparatively analyzed to assess the compatibility of NFTs with the Islamic legal notion of property (māl) as defined in fiqh al-muʿāmalah (Islamic commercial law). The findings suggest that NFTs may be classified as legitimate property according to several contemporary scholars, as they possess economic value, market-recognized benefits, and exclusivity of ownership despite their non-physical form. Nevertheless, the validity of NFT transactions remains conditional: they are lawful only if the represented object is ḥalāl, free from gharar (excessive uncertainty) and maysir (gambling), and uses a Sharia-compliant payment medium. The use of non-compliant cryptocurrencies may invalidate the transaction. This paper argues that NFTs can be recognized as a modern form of Islamic ownership, provided that their use aligns with the principles of prudence, wealth protection (ḥifẓ al-māl), and harm prevention (mafsadah).  Keywords: Al-milkiyyah; Ownership; NFT; Uṣūl al-Fiqh; Fiqh al-Muʿāmalah; Digital Assets